2004
DOI: 10.1002/ajmg.a.20674
|View full text |Cite
|
Sign up to set email alerts
|

Growth, behavior, and clinical findings in 27 patients with Kabuki (Niikawa–Kuroki) syndrome

Abstract: This study was undertaken to document the phenotype of Kabuki (Niikawa-Kuroki) syndrome in patients from Australia and New Zealand, with particular emphasis on growth patterns, behavior, and relationship between head circumference and intellectual level. Data on 27 children and adults with Kabuki (Niikawa-Kuroki) syndrome from Australia and New Zealand were collected by questionnaire and clinical assessment. The patients ranged in age from 7 months to 36 years with a mean age of 7 years and 2 months. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 11 publications
5
88
1
2
Order By: Relevance
“…1,2 The prevalence was estimated to be 1/32,000 in Japan 3 and 1/86,000 in Australia and New Zealand. 4 Although most cases were sporadic, at least 14 familial cases have been reported. It is thought that KS is an autosomal dominant disorder considering the equal male-to-female ratio of patients and parent-child transmission pattern in some familial cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The prevalence was estimated to be 1/32,000 in Japan 3 and 1/86,000 in Australia and New Zealand. 4 Although most cases were sporadic, at least 14 familial cases have been reported. It is thought that KS is an autosomal dominant disorder considering the equal male-to-female ratio of patients and parent-child transmission pattern in some familial cases.…”
Section: Introductionmentioning
confidence: 99%
“…5 The cause of KS remains unknown, even though at least 400 patients have been known in a variety of ethnic groups since 1981. [3][4][5][6][7] Some works have ruled out several loci, e.g., 1q32-q41, 8p22-p23.1 and 22q11, from the candidate for KS. [8][9][10][11][12][13] A study of array-based comparative genomic hybridization (CGH) showed a disruption of C20orf133(MACROD2) gene by ~250 kb deletion on a patient with KS 14 , but the following mutation screening for the gene failed to find pathogenic base change within exons in other 19 patients with KS 14 and in 43 Japanese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Because of mental retardation, in addition to having a cleft palate, language acquisition is often delayed, causing difficulties with communication [18,19]. In addition, occlusal abnormalities are observed because of jaw deformation derived from having a cleft palate, requiring orthognathic surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Endocrine disorders are multiple, deficiency in growth hormone [23] is frequent, and it is to seek when we have short stature smaller than -3DS and recurrent hypoglycemia [24]. The occurrence of early puberty [25,26] is found in 25-43% of cases. Thyroid disorders (hypo-or hyperthyroidism) and the LH deficiency are possible but uncommon.…”
Section: Discussionmentioning
confidence: 99%